The Solomon Islands : 2009 Article IV Consultation; Staff Report; Staff Statement; Supplement to the Staff Report; Public Information Notice; Statement by the Executive Director for the Solomon Islands. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that economic conditions in the Solomon Islands have weakened in 2009, given the effects of the global recession and a logging sector decline. Real GDP growth is projected at 0.4 percent in 2009, compared with 6.9 percent in 2008. On the positive side, inflation pressures have eased substantially, mainly owing to lower fuel and food prices. Executive Directors have advised the authorities to address the increasingly unsustainable fiscal situation, given possible permanent losses in logging-related revenues, relatively large expenditure outlays, and government financing constraints.